"All Human Beings are of Equal Status Since Birth": Caste, Inequality and B.R. Ambedkar's Universal Claim for Human Equality. Issue 3 (December 2020) - Yadav, Vivek Kumar; Dasgupta, Shomik; Kumar, Bharath
Focusing on caste-based oppression, B.R. Ambedkar made a universal claim for human equality and dignity which appeared long before the Universal Declaration of Human Rights. Taking the case of the Mahad movement, we argue that Ambedkar developed a significant egalitarian approach by pointing out how the caste system perpetuated existing inequalities. This article, specifically, aims to explore two central questions: first, what was the central focus of Ambedkar's concerns at Mahad? Second, how can these concerns then provide a better understanding of his approach, with inequality and articulation of human equality and dignity? This article concludes that Ambedkar offered a distinct anti-caste philosophy and charted out a new path of civic and social liberation. His actions had moral philosophical implications for the question, what it fundamentally means to be a human, and what are the social processes that lead to the coming of an egalitarian society. From this philosophical standpoint, Ambedkar formulated the ethics of everyday social life.